PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN ELEKTRONIK WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Produk Mixue di Kota Bogor) - Rafli Arjuna Kusumanegara (2023)
Currently frozen beverage sales in Indonesia are indicated to change over time, fluctuating from year to year, besides that Indonesia is number one as a country that consumes the most frozen drinks and ice cream in Southeast Asia, This study is a quantitative study, conduct aims to find out whether the variable Purchasing decision is influenced by Product Quality variables, Brand Image, and Electronic Word of Mouth. By using non-probability sampling techniques and purposive sampling methods. Data collection is carried out by distributing questionnaires online and offline to prospective respondents. The analysis tool used is SmartPLS 3.0.0. Furthermore, the results obtained from this study show that product quality variables and brand image have a significant influence on purchasing decisions. Electronic Word of Mouth has no significant effect on purchasing decisions